Correa Sutil, Sofía. 2005. Con Las Riendas Del Poder. La Derecha Chilena En El Siglo Xx. Santiago: Editorial Sudamericana, 313 Pp. - Gamboa, Ricardo (Revista de Ciencia Política, 2019)
Sin resumen disponible